Karen Kilimnik - early drawings 1976-1998 - Frey, Patrick 1949-; Koller, Andreas 1983- (Edition Patrick Frey, 2023)
Karen Kilimnik’s artist’s book Early Drawings 1976–1998 is kind of a prequel to Kilimnik’s Drawings, also published by Edition Patrick Frey in 1997. Early Drawings 1976–1998 brings together the artist’s own rich and varied selection of around 130 never before published early works on paper. Detailed, finely worked pastel drawings created between 1976 and 1998 are presented along with ink drawings and other work from that same period; together they illuminate the scope, complexity and virtuosity of Kilimnik’s thematic world